A multilayer screening approach toward the discovery of novel Pf-DHFR inhibitors. (June 2016) - Bagchi, Sourav; Kumar, Manoj; Sharma, Anuj
Graphical abstract: A library of xanthone like natural products was explored through multilayer screening. The initial hits were subjected to similarity based search to find out commercially available compounds. Highlights: 300 xanthones were docked against Pf -DHFR-TS. Size effect on potency was considered. Contact footprints were generated. X5, X113A andX164B were hits with contact footprints similar to known actives. Final selection of 11 compounds from ZINC database. Abstract: A small yet diverse xanthone library was build and computationally docked against wild type Pf -DHFR by Molegro Virtual Docker (MolDock). For analysis of results an integrated approach based on re-ranking, scaling (based on heavy atom counts), pose clustering and visual inspection was implemented. Standard methods such as self-docking (for docking), EF analysis, average rank determinations (for size normalization), and cluster quality indices (for pose clustering) were used for validation of results. Three compoundsX5, X113A andX164B displayed contact footprints similar to the known inhibitors with good scores. Finally, 16 compounds were extracted from ZINC data base by similarity based screening, docking score and drug/lead likeness. Out of these 16 compounds, 11 displayed very close contact footprints to experimentally known inhibitors, indicating there potential utility in further drug discovery efforts.